Development of Employee Work Sheets based Inquiry for Increasing the Ability of Critical Thinking - Ranny Putri Yoma; Armiati Armiati; Edwin Musdi (Fakultas Ilmu Pendidikan UNP)
This study originated from the critical thinking ability of mathematical learners who are still low. The low critical mathematical thinking ability is due to the unavailability of student worksheets that can support the improvement of critical thinking skills of mathematical learners. The learning process has not been able to help learners to build and develop their knowledge in finding their own principles / procedures of mathematics. The purpose of this study is to produce an inquiry-based learner workbook to improve the critical thinking skills mathematically learners class VIII SMP / MTs. The development research carried out uses the Plomp development model. This Plomp development model consists of three phases, namely the initial investigation phase, prototype development phase and assessment phase. Learning worksheets developed based on inquiry. Based on the development that has been done, obtained the sheet of students of mathematics-based inquiry for class VIII SMP / MTs that meet the preliminary research criteria.